Common bean breeding for resistance against biotic and abiotic stresses : From classical to MAS breeding - Miklas, PN; Kelly, James D.; Beebe, Stephen E.; Blair, Matthew W. (Springer, 2006)
Breeding for resistance to biotic and abiotic stresses of global importance in common bean is reviewed with emphasis on development and application of marker-assisted selection (MAS). The implementation and adoption of MAS in breeding for disease resistance is advanced compared to the implementation of MAS for insect and abiotic stress resistance. Highlighted examples of breeding in common bean using molecular markers reveal the role and success of MAS in gene pyramiding, rapidly deploying resistance genes via marker-assisted backcrossing, enabling simpler detection and selection of resistance genes in absence of the pathogen, and contributing to simplified breeding of complex traits by detection and indirect selection of quantitative trait loci (QTL) with major effects. The current status of MAS in breeding for resistance to angular leaf spot, anthracnose, Bean common mosaic and Bean common mosaic necrosis viruses, Beet curly top virus, Bean golden yellow mosaic virus, common bacterial blight, halo bacterial blight, rust, root rots, and white mold is reviewed in detail. Cumulative mapping of disease resistance traits has revealed new resistance gene clusters while adding to others, and reinforces the co-location of QTL conditioning resistance with specific resistance genes and defense-related genes. Breeding for resistance to insect pests is updated for bean pod weevil (Apion), bruchid seed weevils, leafhopper, thrips, bean fly, and whitefly, including the use of arcelin proteins as selectable markers for resistance to bruchid seed weevils. Breeding for resistance to abiotic stresses concentrates on drought, low soil phosphorus, and improved symbiotic nitrogen fixation. The combination of root growth and morphology traits, phosphorus uptake mechanisms, root acid exudation, and other traits in alleviating phosphorus deficiency, and identification of numerous QTL of relatively minor effect associated with each trait, reveals the complexity to be addressed in breeding for abiotic stress resistance in common bean.